The Pricing of Goods and Agricultural Land in Multiregional General Equilibruim - John M. Hartwick (Queen's University, Department of Economics, 1970)
Von Thunen taught us, with the aid of a simple model (15), how to allocate and price agricultural land around a town. Cournot (1), Enke(3), and Samuelson(10) demonstrated how to price commodities at different points in space so as to cause efficient interregional trade to result when transportation costs impede the flow of commodities. The major part of this paper is concerned with the elucidation of the Von Thunen equilibrium and illustrates the power of the Cournot-Samuelson approach.
Keywords: 330